TEKNIK BERMAIN, BERDISKUSI DAN MELANTUNKAN (BBM) AL-QUR’AN DALAM PENINGKATAN PENERAPAN ILMU TAJWID - Ani Kartika (Asaatidzah, 2022)
Tajweed science guides Muslims to know about the procedures for reciting Allah's verses properly and correctly, and so that their meaning is maintained. So that it is expected that by learning tajwid, not only know about the rules of reading the Koran, but also can understand and apply the contents of the contents of the Qur'an in everyday life. The purpose of this study is to obtain an overview of planning learning implementation, evaluation, supporting factors and inhibitors of the BBM Al-Qur’an technique in improving the application of recitation science for seventh grade students at SMPN 3 Cipatat, West Bandung. The research method used is descriptive method with a qualitative approach. The results of the study show that (1) Al-Qur’an learning planning has been going well; (2) the implementation of Al-Qur’an learning has run; (3) evaluating the technical implementation of BBM Al-Qur’an already good enough, where evaluation is carried out systematically and continuously; (4) supporting factors in the implementation of Al-Qur’an learning are professional teachers, young students, Al-learning techniques pleasant, and adequate facilities and infrastructure. Whereas the inhibiting factors stem from students 'abilities, students' interest in learning, students 'talent, parents' motivation, limited learning time and learning.